2009
DOI: 10.1097/fbp.0b013e328330c779
|View full text |Cite
|
Sign up to set email alerts
|

Binge drinking in undergraduates: relationships with sex, drinking behaviors, impulsivity, and the perceived effects of alcohol

Abstract: Binge drinking on university campuses is associated with social and health-related problems. In order to determine the factors that may predict this behavior, we collected information on alcohol use, alcohol expectations, and impulsivity from 428 undergraduate students attending a Canadian university. The subjective effects of a binge-drinking dose of alcohol were assessed in a subset of participants. In the larger sample, 72% of students reported drinking at or above binge drinking thresholds on a regular bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 53 publications
(78 reference statements)
8
67
0
15
Order By: Relevance
“…Also consistent with Government concerns regarding harmful drinking in young people, negative consequences of alcohol use were commonly endorsed but varied in their severity, with 'frequent' or 'normal' consequences occurring in a large majority of students (such as vomiting, having a hangover or missing class) and a smaller subgroup of rarer but more severe consequences (alcohol related violence, law-breaking, property damage, driving when intoxicated). With regards to gender, similar to previous studies (Balodis, Potenza, & Olmstead, 2009;Waldeck & Miller, 1997) we found gender differences in impulsivity and drink choice, although we found only subtle differences in the direct and mediated effects of impulsivity and alcohol-related negative consequences between males and females. This is consistent with other findings (Balodis et al, 2009;Magid et al, 2007) and suggests that while there may be differences between male and female UK university students in specific personality traits and drink choices, these may have only a limited role in explaining variance negative consequences of alcohol use.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Also consistent with Government concerns regarding harmful drinking in young people, negative consequences of alcohol use were commonly endorsed but varied in their severity, with 'frequent' or 'normal' consequences occurring in a large majority of students (such as vomiting, having a hangover or missing class) and a smaller subgroup of rarer but more severe consequences (alcohol related violence, law-breaking, property damage, driving when intoxicated). With regards to gender, similar to previous studies (Balodis, Potenza, & Olmstead, 2009;Waldeck & Miller, 1997) we found gender differences in impulsivity and drink choice, although we found only subtle differences in the direct and mediated effects of impulsivity and alcohol-related negative consequences between males and females. This is consistent with other findings (Balodis et al, 2009;Magid et al, 2007) and suggests that while there may be differences between male and female UK university students in specific personality traits and drink choices, these may have only a limited role in explaining variance negative consequences of alcohol use.…”
Section: Discussionsupporting
confidence: 75%
“…With regards to gender, similar to previous studies (Balodis, Potenza, & Olmstead, 2009;Waldeck & Miller, 1997) we found gender differences in impulsivity and drink choice, although we found only subtle differences in the direct and mediated effects of impulsivity and alcohol-related negative consequences between males and females. This is consistent with other findings (Balodis et al, 2009;Magid et al, 2007) and suggests that while there may be differences between male and female UK university students in specific personality traits and drink choices, these may have only a limited role in explaining variance negative consequences of alcohol use.…”
Section: Discussionsupporting
confidence: 75%
“…Research, previous Canadian studies included, has consistently demonstrated that among university students, male students are more likely to engage in binge drinking compared to their female counterparts (e.g., Adlaf et al, 2005;Balodis et al, 2009;Carlson et al, 2010;Gliksman et al, 1997Gliksman et al, , 2003Tavolacci et al, 2016).…”
Section: Gendermentioning
confidence: 99%
“…However, other researchers have elaborated upon this definition, and have further operationalized and supported the need to consider binge drinking as a gendered concept (e.g., Balodis et al, 2009;D'Alessio, Baiocco, & Laghi, 2006;Delucchi, Matzger, & Weisner, 2008;Simons, Christopher, & Mclaury, 2004;Wechsler, Dowdall, Davenport, & Rimm, 1995).…”
Section: Binge Drinking Operationalizedmentioning
confidence: 99%
See 1 more Smart Citation